The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/slct.202202765
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Electronic Influence of β‐Br Substitutions in CuTPP on Electrochemical Overall Water Splitting in Alkaline Medium

Abstract: Beta substitution has a marked influence on the electronic environment of porphyrin ring atoms and the structure of the substituted porphyrin. In this work, we explore the influence of the bromo (Br) substitution at the β‐positions of copper tetraphenylporphyrin (CuTPP) and its consequent influence on the electrocatalytic alkaline overall water splitting. The β‐Br substitution is expected to exercise a strong influence on the electronic environment of central Cu through the electronic effects of Br. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Ravi Kumar et al reported the various b substituted porphyrins and explored their use in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). 111 Takao Sasaki and coworkers reported manganese porphyrin dimers for use in homogeneously electrocatalytic OER (Fig. 11).…”
Section: Porphyrin Based Mofs For the Electrocatalytic Oxygen Reducti...mentioning
confidence: 99%
“…Ravi Kumar et al reported the various b substituted porphyrins and explored their use in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). 111 Takao Sasaki and coworkers reported manganese porphyrin dimers for use in homogeneously electrocatalytic OER (Fig. 11).…”
Section: Porphyrin Based Mofs For the Electrocatalytic Oxygen Reducti...mentioning
confidence: 99%